Adoption of Moys Classification and Thesaurus (MCT) for Legal Materials: A Survey of Federal University Law Libraries in South East Nigeria. Issue 1 (2nd January 2020) - Chidi Okoye, Nuel-Jean
Abstract: The study investigated the adoption of Moys Classification and Thesaurus for legal materials in the two federal university law libraries in South East Nigeria. Among the objectives included discovering the perspective of library patrons towards the effect of the new scheme. Descriptive survey was used as the research design. The population of this study comprises of all the 10 catalogers and 40 patrons selected by simple random sampling from both libraries, totaling 50. There was no sample due to the population size. The findings of the study revealed that the scheme is currently adopted in the libraries under study.